Evaluation of cascaded voltage step‐up cells applied to the quasi‐Z‐source DC–DC converter. Issue 15 (2nd September 2020) - Faistel, Tiago Miguel Klein; Guisso, Ronaldo Antonio; Andrade, António Manuel Santos Spencer
Abstract : This study presents a set of four cascaded step‐up DC–DC converter with the quasi‐Z source (qZS). By associating the voltage step‐up cells at the input that qZS converter, depending on the configuration, their gain can multiply different factors that each cell with the qZS converter voltage gain. In addition, voltage and current stresses on components change. To evaluate the proposed converters the following characteristics are observed: the principle of operation, the voltage gain of the converters, low voltage and comparative evaluation. In order to demonstrate the simplicity of operation of the proposed converters to higher‐order topology, qZS with boost factor and super‐lift cells is modelled and controlled. Finally, to validate the theoretical analyses, two prototypes of 200 W were implemented experimentally.